EFEKTIVITAS PEMERINTAHAN TRANSFORMASIONAL DALAM MENINGKATKAN KETERLIBATAN MASYARAKAT DESA: STUDI DI MAIWA KABUPATEN ENREKANG - Haeruddin, Haeruddin; Nonci, Nurjannah; Erfina, Erfina; Sam, Muliani (Governance, 2025)
This research aims to analyze the factors that influence community participation in village governance and the role of the village government in increasing such participation. This study also examines the relationship between village government leadership, transparency, public services, and coordination with community leaders on the level of community participation in village development. The method used in this research is a qualitative approach with a descriptive research type. Data were collected through in-depth interviews, observation, and documentation studies. The data were analyzed using thematic analysis. The collected data were analyzed using thematic analysis to identify patterns that exist among the variables studied. The results showed that transformational leadership, transparency, and active community participation play a significant role in improving the quality of village governance. Communities tend to participate more actively in village meetings and decision-making when there is clarity of information and good public services. In addition, the role of community leaders and the use of information technology also have a positive impact on the community participation process. The implication of this study is the importance of increasing the capacity of village governments in improving transparency mechanisms and public services, as well as strengthening coordination with community leaders to expand community participation.